User perception of gaming element effectiveness in a corporate learning application - Arnold, Henry (Department of Computer Science, 2018)
This Conversion Masters in Information Technology thesis gathered users' perceptions about eight gaming elements to determine their effectiveness on aspects of playability, enjoyment and intrinsic motivation needed in a gamified corporate learning application. The study focused on user opinions about a Progress Bar, Individual Leaderboard, Departmental Leaderboard, Timer, In-Game Currency, Badges, Storyline/Theme and Avatar. A gamification application containing these gaming elements was designed and developed to make the evaluation. The application entailed users learning four Information Technology Infrastructure Library (ITIL) processes needed to manage an information technology department in a telecommunications company. The application design process considered the business goals, rules, target behaviours, time limits, rewards, feedback, levels, storytelling, interest, aesthetics, replay or do-overs, user types, activity cycles, fun mechanisms and development tools needed to create a coherent, addictive, engaging and fun user experience. Player types were determined using the Brainhex online survey. Federoff's Game Playability Heuristics model was used to measure the users' perceptions about the playability of the application. Sweetser and Wyeth's Gameflow model was used to measure perceptions about the gaming elements' contribution toward creating an enjoyable experience. Malone and Lepper's Taxonomy of Intrinsic Motivation for Learning was used to measure the gaming elements' ability to promote an intrinsically motivating learning environment. Masterminds, Achievers, Conquerors and Seekers were the most prominent player types found in the Brainhex online survey for which the gamification application design then catered. The staff in the department play-tested the application to evaluate the gaming elements. Overall the Storyline/Theme, suited to Seekers and Masterminds, ranked as the most effective gaming element in this study. The users perceived artwork as an essential component of a gamified learning application. The Individual Leaderboard, suited to Conquerors, ranked very closely as the second most effective gaming element. The Storyline/Theme and Individual Leaderboard both performed the strongest against the criteria measuring the playability. The Storyline/Theme was by far the strongest from a gameflow perspective and the Individual Leaderboard from a motivation perspective. The Avatars ranked the worst across all the measurement criteria. Based on quiz results, 86 percent of the staff in the department had learned the material from the gamified training prototype developed in this work. The findings from this study will therefore serve as input for developing a full-scale gamification learning application.